2013
DOI: 10.3892/or.2013.2714
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 1 is a tumor-associated antigen in esophageal squamous cell carcinoma

Abstract: Peroxiredoxin 1 (Prdx1) is an antioxidant and plays an important role in H2O2-mediated cell signaling. We previously found that the expression level of Prdx1 was elevated in esophagus squamous cell carcinoma (ESCC) tissue using a proteomics approach. Since overexpressed protein can induce an autoimmune response, to further examine whether serum from ESCC patients exhibits immunoreactivity against Prdx1, autoantibody responses to Prdx1 were evaluated by ELISA, western blotting and indirect immunofluorescence as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…23,24 Ren et al 23 reported that Prx-1 as a tumor-associated antigen may conduce to malignant transformation in esophageal squamous cell carcinoma. Ha et al 24 revealed that Prx-1 excessive expression promotes epithelialemesenchymal transition (EMT) and cellular migration by inducing transforming growth factor beta1 (TGF-b1) in cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Ren et al 23 reported that Prx-1 as a tumor-associated antigen may conduce to malignant transformation in esophageal squamous cell carcinoma. Ha et al 24 revealed that Prx-1 excessive expression promotes epithelialemesenchymal transition (EMT) and cellular migration by inducing transforming growth factor beta1 (TGF-b1) in cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, these have been lacking in clinical usefulness because their sensitivity and specificity entertain values of < 70%, although many autoantigens may be detected by antibody-based methods and are considered candidates for oncogenic proteins [10,11,[20][21][22][23][24][25][26][29][30][31][32][33][34][35][38][39][40]. Validation of the most promising biomarkers proposed for the breast cancer diagnosis and prognosis has required the application of high evaluation standards in prospective cohort studies of women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Using a proteomics approach has allowed the identification of autoantibodies against annexin-I, annexin-II [22], peroxiredoxin-I [23], calreticulin [24], and peroxiredoxin-VI [25], which have been found in the sera of patients with lung, pancreatic, and liver cancer. The presence of autoantibodies in serum against several tumor antigens, such as p53, embryonic neural proteins, and antineural/antinuclear antigens, has been also evaluated in breast cancer [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic study has found that the expression level of PRDX1 is elevated in oesophagus squamous cell carcinoma (ESCC) tissue 63. Further study demonstrated that PRDX1 is significantly increased in ESCC tissues compared with the paired adjacent normal tissues 15. In addition, several studies have identified that PRDX1 is overexpressed in ESCC cells compared with the non‐cancerous oesophageal epithelial cells 64, 65.…”
Section: Prdx1 and Oesophageal Cancermentioning
confidence: 99%
“…In addition to its peroxidase and chaperone functions, PRDX1 could also enhance natural killer cell cytotoxicity and suppress oncogenic proteins such as c‐Myc and c‐Abl 11, 12, 13. Recent studies have shown that abnormal expression of PRDX1 has been observed in several human cancers, including breast, oesophageal, lung and prostate cancers 14, 15, 16, 17. Furthermore, PRDX1 also regulates several ROS‐dependent signalling pathways and is thought to be a key intracellular intermediate balancing cell survival and apoptosis 7, 18.…”
Section: Introductionmentioning
confidence: 99%